Uma voz para a América Latina? A elaboração discursiva da vida de Mercedes Sosa em documentários biográficos - Souza, Nathan Bastos de (Universidade Federal de São Carlos, 2021)
Mercedes Sosa (1935-2009) was an Argentine singer who was fundamental in the development of Latin American music with a social perspective and her political activity raised the militant content of the songs. In this thesis we study the biographical discourse about her in three documentaries "Mercedes Sosa - Como un pájaro libre", directed by Ricardo Wüllicher, 1983, "Mercedes Sosa - ¿Será posible el sur?" directed by Stefan Paul, 1985, and “Mercedes Sosa, la voz de Latinoamérica”, by Rodrigo Vila, 2013. In this sense, the research is guided by a question: how is Mercedes Sosa's life elaborated discursively in the biographical documentaries and what are the elements considered valid in her profile to elevate her to the condition of “voz da América Latina”? The main aim of the thesis is to study the discursive elaboration of Mercedes Sosa's life in biographical documentaries in order to understand how this idea of the “voz da América Latina”, with the goal to contribute theoretically to a recent reflection about discourse in Bakhtinian studies. We unfold this main aim into three others specifics, what are, to characterize the biographical discourse, from a historical, epistemological and discursive point of view, producing an examination of its discursive functioning; to study the discursive elaboration of Mercedes Sosa's life as it is presented in the documentaries in analysis; discuss the meanings of the epithet “voz da América Latina” in the comparison between moments of emergence and permanence after the singer's death. The theoretical-methodological approach will be based mainly on the discussion of the authors of the Bakhtin Circle (BAKHTIN, 2011, 2015, MEDVIÉDEV, 2012, VOLÓCHINOV, 2017) on the meeting of discourses, through comparison, based on the notions of transmission, understanding and evaluation of the speech of the other. We organized the thesis in three parts. In part I, we characterize the biographical discourse and delimit the ways to understand it; in part II, we analyze fragments of chronologically organized documentaries and perceive the affirmation of conditioning elements for the epithet “a voz da América Latina”; in part III, we present the emergence and permanence of the epithet from an analysis of its meanings, we consider that this part contains the validating elements for Mercedes Sosa to be considered “a voz da América Latina”. Finally, we enunciate the thesis defended in this work: her voice, the militant content of the songs, the historical-political period, the previous life, the political struggle, the Latin American connection are ingredients in the discursive elaboration of Mercedes Sosa's life in the biographical documentaries and help to consolidate the edifying values related to the epithet “voz da América Latina”. The combination of these factors legitimizes that the name Mercedes Sosa is raised to the status of voice of the continent, once one considers the adherence of her singing profession – despite the other intellectuals and artists active at the same time – her vocal power, the questions that the repertoire presented and, above all, her political action.

Mercedes Sosa (1935-2009) ha sido una cantante argentina fundamental para el desarrollo de una música latino-americana de perspectiva social y su actividad político elevó el contenido militante de las canciones. En esta tesis estudiamos el discurso biográfico a su respecto en tres documentales “Mercedes Sosa - Como un pájaro libre”, con dirección de Ricardo Wüllicher, de 1983, “Mercedes Sosa - ¿Será posible el sur?” dirigido por Stefan Paul, de 1985, e “Mercedes Sosa, la voz de Latinoamérica”, de Rodrigo Vila, de 2013. En ese sentido, la investigación se guía por una cuestión: ¿cómo la vida de Mercedes Sosa es elaborada discursivamente en los documentales biográficos y cuáles son los elementos considerados validadores en su perfil para alzarla a la condición de “voz de América Latina”? El objetivo general de esta tesis es estudiar la elaboración discursiva de la vida de Mercedes Sosa en los documentales biográficos a fín de entender cómo se constituye esa idea de “voz de América Latina”, con vistas a contribuir teóricamente con la reflexión reciente sobre el encuentro de discursos en los estudios bajtínianos. Dividimos ese objetivo general en tres objetivos específicos, cuáles sean, caracterizar al discurso biográfico, de un punto de vista histórico, epistemológico y discursivo, produciendo en examen de su funcionamiento discursivo; estudiar la elaboración discursiva de la vida de Mercedes Sosa tal cual se presenta en los documentales en análisis; discutir los sentidos del epíteto “voz de América Latina” en el cotejo entre los momentos de emergencia y permanencia tras el fallecimiento de la cantante. El abordaje teórico-metodológico se dará conforme, principalmente, la discusión de los autores del Círculo de Bajtín (BAKHTIN, 2011, 2015, MEDVIÉDEV, 2012, VOLÓCHINOV, 2017) sobre el encuentro de discursos, por medio del cotejamiento, con base en las nociones de transmisión, comprensión y evaluación del discurso del otro. Organizamos la tesis en tres partes. En la parte I, caracterizamos el discurso biográfico y delimitamos las maneras de comprenderlo; en la parte II, analizamos fragmentos de los documentales cronológicamente organizados y percibimos la afirmación de elementos condicionantes para el epíteto “la voz de América Latina”; en la parte III, presentamos la emergencia y la permanencia del epíteto a partir de un análisis de sus sentidos, consideramos que esa parte contiene los elementos validadores para que Mercedes Sosa fuera considerada “la voz de América Latina”. Finalmente, enunciamos la tesis ora defendida en este trabajo: la propia voz, el contenido militante de las canciones, el período histórico-político, la vida anterior, la lucha política, la conexión latinoamericana son ingredientes en la elaboración discursiva de la vida de Mercedes Sosa en los documentales biográficos y auxilian en la sedimentación de los valores edificantes relacionados al epíteto “voz de América Latina”. La conjunción de eses factores legitima que el nombre de Mercedes Sosa se alce a la condición de voz del continente, una vez que se considere la adherencia de su profesión de cantante – a pesar de los demás intelectuales y artistas en actividad en la misma época – su potencia vocal, las cuestiones que el repertorio presentaba y, sobretodo, su acción política.
¿Una voz para América Latina? La elaboración discursiva de la vida de Mercedes Sosa en documentales biográficos
Keywords: Mercedes Sosa; Voz da América Latina; Encontro de discursos; Documentários biográficos; Estudos Bakhtinianos; Voz de América Latina; Encuentro de discursos; Documentales biográficos; Estudios bakhtinianos; Voice of Latin America; Meetings of discourses; Biographical documentaries; Bakhtinian studies; LINGUISTICA, LETRAS E ARTES::LINGUISTICA